Pendampingan Penyusunan Bahan Ajar Ilmu Falak Berbasis Kurikulum Pesantren Muadalah di Dayah Salafiyah Raudhatul Maarif Cot Trueng Aceh Utara - Ismail Ismail; Hasna Tuddar Putri (IHSAN : JURNAL PENGABDIAN MASYARAKAT, 2023)
Pondok Pesantren Raudhatul Ma'arif Cot Trueng is one of the islamic boarding schools in North Aceh Regency, Aceh Province that has organized a muadalah islamic boarding school curriculum system as regulated in PMA. No. 18 of 2014, where the subject of falak science is one of the subjects of the Islamic family that must be taught for the Aliyah level. Limitations in the availability of falak science teaching materials and teaching staff for falak science subjects are the main obstacles in implementing the muadalah curriculum in the Islamic boarding school. This community service program is aimed at aliyah teachers at the Raudhatul Ma'arif Cot Trueng Islamic Boarding School, which teaches falak science subjects, because several problems include: 1) the teachers who teach falak science subjects have not been able to master the falak science material optimally; 2) teachers are not used to compiling teaching materials that are in accordance with the existing curriculum; 3) The lack of falak science literature in Islamic boarding schools causes teachers to be unable to compile teaching materials optimally. From these problems, assistance activities will be sought, especially in compiling teaching materials in accordance with the muadalah curriculum which is a guideline in the implementation of the curriculum at the Raudhatul Ma'arif Islamic boarding school. This assistance aims to allow teachers to teach falak science independently and falak science material can be taught comprehensively based on the teaching materials they have compiled. The result obtained from this assistance is that teachers have been able to understand mastering falak science so that they can produce falak science teaching materials in the form of textbooks that are in accordance with the competencies in the muadalah curriculum. These results are obtained from the results of mentoring starting from the planning stage, action stage, observation and ending with reflection.